Dynamic Chinese Text on a Single-Line Display: Effects of Presentation Mode. - Shieh, Kong-King; Hsu, Sheng-Hsiung; Lin, Yu-Chao (Perceptual & Motor Skills)
There are many technologies with which users must read text from small-screen electronic devices. So, understanding the constraints and optimization of humans' use of these devices is important. In the present study, the optimal ways to display Chinese text on a single-line display were explored. 64 Chinese-speaking Taiwanese undergraduates participated in a 4 × 2 mixed design in which the presentation mode was a between-subjects factor and the text difficulty was a within-subjects factor. Four presentation modes in which two presentation formats, i.e., leading and rapid serial visual presentation, combined with two text layouts, i.e., convention and Interword spacing, were investigated. Chinese texts of High Difficulty and Low Difficulty were compared. The results showed that the leading format with Interword spacing resulted in greater reading efficiency and faster preferred reading speed than other presentation modes. Although the reading efficiency and preferred reading speed for Low Difficulty materials were significantly greater than for High Difficulty materials, the interaction between the presentation mode and text difficulty was not significant. The applications for presenting moving Chinese text on a single-line display are briefly discussed. Reprinted by permission of the publisher.